Conservation of ancient constructions and application to a masonry arch bridge - Lourenço, Paulo B. (2006)
In the last years significant developments occurred with respect to the possibilities of analysis of ancient cultural heritage buildings, which result from the societal growing concern about the preservation of this heritage, together with the evident cultural and economic importance of this activity. Recommendations for interventions in architectural heritage structures recently issued by ICOMOS are briefly reviewed here, with a discussion about the proposed methodology. Then, a case study is fully detailed. In this case, the aspects of survey, numerical analysis, justification of remedial measures, detailing of the adopted strengthening and works carried out of a historical masonry arch bridge are described.